2016
DOI: 10.1016/j.yjmcc.2015.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and fibrotic responses of cardiac fibroblasts to myocardial damage associated molecular patterns (DAMPs)

Abstract: Cardiac fibroblasts (CF) are well-established as key regulators of extracellular matrix (ECM) turnover in the context of myocardial remodelling and fibrosis. Recently, this cell type has also been shown to act as a sensor of myocardial damage by detecting and responding to damage-associated molecular patterns (DAMPs) upregulated with cardiac injury. CF express a range of innate immunity pattern recognition receptors (TLRs, NLRs, IL-1R1, RAGE) that are stimulated by a host of different DAMPs that are evident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(129 citation statements)
references
References 158 publications
(257 reference statements)
0
124
0
1
Order By: Relevance
“…In addition to Ca 2+ dyshomeostasis, TNF-α also causes direct cytotoxicity [35], oxidative stress [36], disruption of excitation-contraction coupling [37], up-regulation of other cardiac suppressing cytokines (e.g., IL-1β) [38,39] and induction of cardiomyocyte apoptosis [40], all of which impair cardiac contractile function in cardiomyocytes, isolated hearts and intact animals. Pro-inflammatory response may also promote fibrosis in heart [41,42]. Having shown that disruption of calpain inhibited ER stress, we further demonstrated that deletion of capns1 prevented pro-inflammatory cytokines expression in HFD-fed mouse hearts and silencing of capn1 inhibited palmitate-induced pro-inflammatory response in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 63%
“…In addition to Ca 2+ dyshomeostasis, TNF-α also causes direct cytotoxicity [35], oxidative stress [36], disruption of excitation-contraction coupling [37], up-regulation of other cardiac suppressing cytokines (e.g., IL-1β) [38,39] and induction of cardiomyocyte apoptosis [40], all of which impair cardiac contractile function in cardiomyocytes, isolated hearts and intact animals. Pro-inflammatory response may also promote fibrosis in heart [41,42]. Having shown that disruption of calpain inhibited ER stress, we further demonstrated that deletion of capns1 prevented pro-inflammatory cytokines expression in HFD-fed mouse hearts and silencing of capn1 inhibited palmitate-induced pro-inflammatory response in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, FN circulates in the soluble form in plasma or accumulates in tissue as insoluble ECM components (32). There is a marked upregulation of FN in the plasma during inflammatory conditions (33,34), and there is extravasation of this plasmatic protein in the basement membrane of the inflamed tissue (35). Moreover, FN has the ability to act as an endogenous ligand for TLR4 and to activate its signaling pathway, which leads FN-PMN).…”
Section: Discussionmentioning
confidence: 99%
“…Fibroblasts are abundant in the heart and have multiple potential roles during myocardial inflammation and repair that follows MI (Porter & Turner 2009). In addition to the production of collagen and other matrix proteins that determine scar integrity, they secrete molecules, including cyto­kines, prostaglandins (Shinde & Frangogiannis 2014, Fernando et al 2015, Turner 2016) and microRNA (Fang & Yeh 2015), capable of regulating inflammation (Porter & Turner 2009, Chen & Frangogiannis 2013, van Nieuwenhoven & Turner 2013), Treg recruitment (Frangogiannis 2014), angiogenesis (Newman et al 2011), cardiogenesis (Furtado et al 2014) and hypertrophy (Abonnenc et al 2013, Cartledge et al 2015). The role of cardiac fibroblast 11β-HSD1 in regulating the cellular secretome and on the response to MI and other pathological challenges merits further investigation.…”
Section: β-Hsd1 MI and Heart Failurementioning
confidence: 99%